SCHISTOSOMIASIS MANSONI IN THE "BAIXADA OCIDENTAL MARANHENSE", STATE OF MARANHÃO, BRAZIL: CROSS-SECTIONAL STUDIES PERFORMED IN 1987 AND 1993 - Raimundo Nonato Martins CUTRIM; Pedro Paulo CHIEFFI; José Cássio de MORAES (Revista do Instituto de Medicina Tropical de São Paulo, 1998)
A cross-sectional study on the prevalence of schistosomiasis mansoni in three sites of the "Baixada Ocidental Maranhense" was carried out in 1993 in: Alegre (in the municipality of São Bento), Aliança (in Cururupu) and Coroatá II (in the municipality of São João Batista). Results were compared to those of another study performed at the same sites and in similar conditions, in 1987. The entire population of the three sites, with few exceptions, was submitted to fecal tests using the Kato-Katz method and immediate intradermal tests for schistosomiasis in both studies. Subjects with positive results in one of these tests were clinically evaluated by a physical examination. In 1993, the total of 827 subjects were submitted to fecal examination and 826 to intradermal test. Schistosoma mansoni eggs were found in the feces of 154 (18.6%) subjects, while 478 (57.9%) subjects presented a positive intradermal test. Stool examination was carried out in 367 subjects in Alegre with a positivity rate of 14.9%; the intradermal test, performed in 366 subjects, was positive in 47.5% of the cases. In Aliança, 277 subjects had their feces examined and were submitted to an intradermal test, with a positivity rate of 34.4% and 70.7%, respectively. Finally in Coroatá II, 183 inhabitants submitted to fecal and intradermal tests had positivity rates of 2.2% and 59.0%, respectively. When the present data were compared to those obtained in the survey performed in 1987, a significant decrease in the prevalence of infection by S. mansoni was observed in Alegre and Coroatá II, and a prevalence increase in Aliança. Esquistossomose mansoni na Baixada Ocidental Maranhense, Estado do Maranhão, Brasil: estudos transversais realizados em 1987 e 1993 Realizou-se, em 1993, estudo transversal acerca da ocorrência de esquistossomose mansoni em três localidades da Baixada Ocidental Maranhense: Alegre (município de São Bento), Aliança (município de Cururupu) e Coroatá II (município de São João Batista). Os resultados foram cotejados aos de outro estudo, efetuado nas mesmas localidades e em condições semelhantes, em 1987. Em ambos os estudos, salvo poucas exceções, toda a população das três localidades foi submetida a exame parasitológico de fezes, pelo método de Kato-Katz e a intradermorreação para esquistossomose. Os indivíduos que apresentaram resultado positivo em algum desses exames foram avaliados clinicamente, por meio de exame físico. Em 1993, ao todo, 827 pessoas foram submetidas a exame de fezes e 826 a intradermorreação. Nas fezes de 154 (18,6%) encontraram-se ovos de Schistosoma mansoni e 478 (57,9%) apresentaram reação intradérmica positiva. Em Alegre o exame parasitológico de fezes foi realizado em 367 indivíduos, com índice de positividade de 14,9% e a intradermorreação, efetuada em 366 indivíduos, foi positiva em 47,5% dos casos. Em Aliança, 277 indivíduos foram examinados por exame de fezes e intradermorreação apresentando taxas de positividade de, respectivamente, 34,4% e 70,7%. Finalmente, em Coroatá II 183 moradores submetidos a exame de fezes e intradermorreação revelaram índices de positividade de 2,2% e 59,0%, respectivamente. Quando estes dados foram cotejados aos obtidos em inquérito efetuado em 1987 observou-se queda significativa da prevalência de infecção por S. mansoni nas localidades de Alegre e Coroatá II e aumento da prevalência em Aliança.